MODEL READY: SEBUAH PARADIGMA BARU UNTUK MENUMBUHKAN KEMAMPUAN HISTORICAL LITERACY - Shela Dwi Utari; Joko Sayono; Aditya Nugroho Widiadi; Indah Wahyu Puji Utami (Jurnal Pendidikan Sejarah Indonesia, 2026)
Contemporary history education is no longer a subject based on memorising facts; rather, it focuses on equipping students with mastery of the discipline of history. One such aspect is historical literacy, a type of knowledge that lies above mere content or substance comprehension. Historical literacy is the ability to read, compare, and reconstruct historical narratives using historical sources. Problems arise when teachers are still unable to apply these skills in the classroom because there is no specific model to support them. Therefore, in this article, the author proposes a new paradigm in history education, namely the Ready model. The method used to develop the Ready model is the Kemp model, which consists of 9 stages: (1) instructional problems, (2) learner characteristics, (3) task analysis, (4) instructional objectives, (5) content sequencing, (6) instructional strategies, (7) designing the message, (8) development of instruction, and (9) evaluation instruments. The result of this article is the Ready model, which consists of questioning, significance and contextualisation, exploration, judgment and interpretation, and reflection. The Ready model requires students and teachers to interact with modules or textbooks, then trace their sources, and finally construct a simple historiography to determine what differs from previous narratives